Capacity Building for Small Fishermen Ds. Supervisor of Aluh Aluh District, Banjar Prov. South Kalimantan - Isra Ul Huda; Asruni Asruni; Anthonius Junianto Karsudjono (Mandalika Journal of Community Services, 2025)
The research "Development of Small Fishermen's Capacity" is aimed at improving the livelihood of small-scale fishermen in Pemurus Village, Aluh Aluh Subdistrict, Banjar District, South Kalimantan. The project focuses on enhancing the skills, knowledge, and capacity of local fishermen through community service activities. This initiative, led by Isra Ul Huda, Asruni, and Dr. Anthonius Junianto Karsudjono, emphasizes the importance of local economic development and the role of sustainable fishing practices. The program engaged local stakeholders, including the Fisheries and Food Security Office of Banjar District and the Pemurus Village Head, ensuring broad community support. By increasing awareness and providing practical training on sustainable practices, the project seeks to empower local fishermen, enhance their economic opportunities, and promote environmental conservation. The report also discusses the challenges faced and the outcomes achieved through the collaborative efforts between the researchers and the community